Composite coating for FPC reinforced austenitic stainless steel surface and preparation method thereof

By applying a composite coating of glass-silicon carbide bottom layer and polytetrafluoroethylene top layer on the surface of austenitic stainless steel, the problem of insufficient wear resistance of austenitic stainless steel is solved, good wear resistance and self-lubricity are achieved, and service life is extended and the performance of flexible circuit boards is improved.

CN119592108APending Publication Date: 2025-03-11DONGGUAN UNIV OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411555897.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Austenitic stainless steel has poor wear resistance and is difficult to show good performance in the field of flexible circuit board reinforcement.

Method used

A composite coating, including a glass-silicon carbide bottom layer and a polytetrafluoroethylene top layer, is prepared by spray coating and lift coating technology to form a porous structure to improve wear resistance and self-lubricity.

Benefits of technology

It achieves a firm combination of composite coating and stainless steel substrate, has excellent wear resistance and self-lubricity, can maintain a long service life under high loads, and meets the performance requirements of flexible circuit board reinforcement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005116416250000011
    Figure HDA0005116416250000011
  • Figure HDA0005116416250000021
    Figure HDA0005116416250000021
  • Figure HDA0005116416250000031
    Figure HDA0005116416250000031
Patent Text Reader

Abstract

The invention relates to the technical field of self-lubricating composite coatings, and discloses a composite coating for the surface of FPC reinforced austenitic stainless steel and a preparation method of the composite coating. The composite coating comprises a glass-silicon carbide bottom layer and a polytetrafluoroethylene surface layer, the glass-silicon carbide bottom layer has a hole structure; and polytetrafluoroethylene is loaded in the holes. The composite coating provided by the invention is provided with the glass-silicon carbide bottom layer with a porous structure, a foundation is provided for constructing a surface lubricating film by loading polytetrafluoroethylene, and the coating has excellent wear resistance, can bear high load within 1.1 GPa, and keeps a relatively long service life; the preparation method of the composite coating is simple in step, a porous structure which is proper in aperture size and uniform in distribution is prepared by controlling the thickness of the glass-silicon carbide porous bottom layer and a sintering process, and then solidification and permeation of polytetrafluoroethylene are realized by a pulling, dipping and drying method, so that the polytetrafluoroethylene is not easy to fall off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of self-lubricating composite coatings, and in particular to a composite coating for FPC reinforced austenitic stainless steel surface and a preparation method thereof. Background Art

[0002] Flexible printed circuit (FPC) is a thin, freely bendable circuit board, which is an indispensable component for lightweight and thin products. However, due to its thin thickness and easy bending, it will cause many problems in practical application. At present, the main method of bonding reinforcement plates is to increase the hardness and thickness of FPC connectors and component assembly parts to increase the strength and stability of flexible printed circuit boards.

[0003] The main materials of common reinforcement plates include stainless steel, polyimide, polyethylene terephthalate and glass epoxy resin. Stainless steel is an iron alloy with added chromium and nickel. Its strength is higher than that of resin. Therefore, as a reinforcement plate, it can achieve ultra-thin thickness. Stainless steel also has the advantages of strong conductivity, forming a grounding loop, and effectively preventing electromagnetic noise. Among them, austenitic stainless steel has good processing properties, and because it usually contains at least 10.5wt% chromium and 8wt% nickel, it exhibits excellent corrosion resistance in oxidizing media, making it an ideal material for reinforcement plates. However, the microstructure of austenitic stainless steel is mainly composed of a soft austenite phase, which is not as good as hard phases such as martensite when subjected to friction and wear, resulting in relatively poor wear resistance of austenitic stainless steel. At present, the wear resistance is mainly improved by increasing the surface hardness to improve its mechanical properties, or by trying to reduce the friction coefficient of the steel surface.

[0004] There are many kinds of process methods to improve the surface hardness of austenitic stainless steel, such as surface quenching, alloying and coating. Among them, coating is widely used because it is independent of alloy substrate elements. In recent decades, ceramic coatings, cemented carbide coatings, diamond-like coatings, etc. have been developed on the surface of steel substrates. Glass ceramics are widely used in the field of surface protection engineering due to their high hardness, strong adhesion and large thermal expansion coefficient. However, the shortcomings of glass ceramic coatings such as high brittleness, high temperature sintering and difficulty in adding lubricating second phases (such as graphite and polytetrafluoroethylene) seriously limit their application.

[0005] The reduction of the friction coefficient of austenitic stainless steel surface is mainly achieved by forming a non-metallic friction surface or adding a solid lubricating film, such as forming nitrides, oxides and carbides on the steel surface, or a surface layer of their composite compounds by nitriding, carbon and oxygen, or by adding calcium fluoride, graphite, molybdenum disulfide, polytetrafluoroethylene and other substances to the coating to construct a surface lubricating film in different temperature ranges. In the lower temperature range (room temperature-200°C), the polytetrafluoroethylene coating has an extremely low friction coefficient. Due to the characteristics of the CF bond, it is difficult for it to adhere to the friction pair, but this also means that it is difficult to bond with the alloy substrate, thus showing poor adhesion. At the same time, its softer properties also make the polytetrafluoroethylene coating on the smooth substrate surface easy to be scraped off.

[0006] Therefore, providing a coating that can firmly bond to the surface of austenitic stainless steel and has good self-lubricity and wear resistance is of great significance for expanding the application of austenitic stainless steel in the field of FPC reinforcement and improving the performance of flexible circuit boards. Summary of the invention

[0007] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a composite coating; the second purpose of the present invention is to provide a method for preparing the composite coating; the third purpose of the present invention is to provide an FPC austenitic stainless steel reinforcement plate.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A first aspect of the present invention provides a composite coating, comprising a glass-silicon carbide bottom layer and a polytetrafluoroethylene surface layer; the glass-silicon carbide bottom layer has a pore structure; and polytetrafluoroethylene is loaded in the pores.

[0010] Preferably, in the glass-silicon carbide bottom layer, the depth of the holes is 7-10 μm; further preferably, the depth of the holes is 8-10 μm.

[0011] Specifically, the hole penetrates the glass-silicon carbide bottom layer, and the hole depth is equal to the thickness of the glass-silicon carbide bottom layer.

[0012] Preferably, in the glass-silicon carbide bottom layer, the average diameter of the holes is 70-170 μm; further preferably, the average diameter of the holes is 75-165 μm.

[0013] Preferably, in the glass-silicon carbide bottom layer, the holes occupy 50-60% of the total area of ​​the glass-silicon carbide bottom layer; further preferably, the holes occupy 50-55% of the total area of ​​the glass-silicon carbide bottom layer.

[0014] Preferably, in the glass-silicon carbide bottom layer, the filling height of polytetrafluoroethylene in the holes is 2-3 μm.

[0015] Preferably, the thickness of the polytetrafluoroethylene surface layer is 1-2 μm.

[0016] Preferably, the composite coating comprises the following preparation raw materials: glass powder, silicon carbide, polytetrafluoroethylene emulsion and dispersant.

[0017] Preferably, the glass powder comprises the following raw materials in mass percentage: 55-65% SiO2, 8-12% B2O3, 3-7% Al2O3, 8-12% Na2O, 3-7% K2O, 3-7% CaO, 1-4% CoO; further preferably, the glass powder comprises the following raw materials in mass percentage: 58-62% SiO2, 10-12% B2O3, 5-6% Al2O3, 10-12% Na2O, 5-6% K2O, 5-6% CaO, 2-4% CoO.

[0018] Preferably, the glass powder is prepared by a method comprising the following steps: ball-milling and mixing the raw materials according to a proportion, smelting, and water-quenching to obtain a glass block; ball-milling and sieving the glass block to obtain the glass powder.

[0019] Preferably, the ball milling mixing speed is 250-350 r / min; further preferably, the ball milling mixing speed is 280-320 r / min.

[0020] Preferably, the ball milling mixing time is 20-40 min; further preferably, the ball milling mixing time is 25-35 min.

[0021] Preferably, the smelting temperature is 1200-1400°C; further preferably, the smelting temperature is 1250-1350°C.

[0022] Preferably, the smelting time is 1-4 hours; further preferably, the smelting time is 2-4 hours.

[0023] Preferably, the speed of ball milling the glass block is 300-500 r / min; further preferably, the speed of ball milling the glass block is 350-450 r / min.

[0024] Preferably, the glass block is ball-milled for 110-130 hours; further preferably, the glass block is ball-milled for 115-125 hours.

[0025] Preferably, the particle size of the glass powder is less than 75 μm; more preferably, the particle size of the glass powder is 70-74 μm.

[0026] Preferably, the diameter of the silicon carbide is 1-3 μm; further preferably, the diameter of the silicon carbide is 1-2 μm.

[0027] Preferably, the dispersant includes an alcohol solvent; further preferably, the alcohol solvent includes anhydrous ethanol.

[0028] Preferably, in the polytetrafluoroethylene emulsion, the content of polytetrafluoroethylene is 50-70wt%; further preferably, the content of polytetrafluoroethylene is 55-65wt%.

[0029] Preferably, in the polytetrafluoroethylene emulsion, the particle size of the polytetrafluoroethylene is 180-200 nm; further preferably, the particle size of the polytetrafluoroethylene is 190-200 nm.

[0030] Preferably, the mass ratio of the glass powder to silicon carbide is (15-25):1; further preferably, the mass ratio of the glass powder to silicon carbide is (18-22):1.

[0031] Preferably, the ratio of the volume of the dispersant to the total mass of the glass powder and silicon carbide is (10-20) mL:1 g; further preferably, the ratio of the volume of the dispersant to the total mass of the glass powder and silicon carbide is (10-15) mL:1 g.

[0032] The second aspect of the present invention provides a method for preparing the composite coating according to the first aspect of the present invention, comprising the following steps:

[0033] S1, mixing glass powder, silicon carbide and a dispersant to obtain a slurry;

[0034] S2, spraying the slurry onto the surface of the stainless steel substrate and curing it to obtain a glass-silicon carbide bottom layer;

[0035] S3, immersing the stainless steel substrate containing the glass-silicon carbide bottom layer in a polytetrafluoroethylene emulsion, and coating the substrate by pulling to obtain the composite coating.

[0036] Preferably, in step S1, the mixing method includes ball milling mixing.

[0037] Preferably, the ball milling mixing speed is 250-350 r / min; further preferably, the ball milling mixing speed is 280-320 r / min.

[0038] Preferably, the ball milling mixing time is 20-40 min; further preferably, the ball milling mixing time is 25-35 min.

[0039] Preferably, in the step S2, the slurry is ultrasonically mixed before spraying.

[0040] Preferably, in step S2, the spraying pressure is 0.2-0.4 MPa; further preferably, the spraying pressure is 0.2-0.2 MPa.

[0041] Preferably, in step S2, the spraying distance is 20-40 cm; further preferably, the spraying distance is 25-35 cm.

[0042] Preferably, in step S2, the curing temperature is 750-850°C; further preferably, the curing temperature is 780-820°C.

[0043] Preferably, in step S2, the curing time is 10-15 min; further preferably, the curing time is 10-12 min.

[0044] Preferably, in the step S2, the step of heat treating the substrate at 95-105° C. to remove the solvent before curing is performed.

[0045] Preferably, in step S3, the immersion time is 1-2 min / time; further preferably, the immersion time is 1-1.5 min / time.

[0046] Preferably, in step S3, the speed of pulling the coating is 2-4 mm / min; further preferably, the speed of pulling the coating is 2-3 mm / min.

[0047] Preferably, in step S3, the interval of pulling the coating is 2-4 minutes; further preferably, the interval of pulling the coating is 2-3 minutes.

[0048] Preferably, in step S3, the number of times the coating is pulled up is 2-4 times; further preferably, the number of times the coating is pulled up is 2-3 times.

[0049] Preferably, in step S3, after the Czochralski coating is completed, the composite coating is kept warm for 2-3 hours at 450-400°C and a vacuum degree of 9-11 kPa. This operation can ensure that polytetrafluoroethylene can be well consolidated and infiltrated in the microscopic pore structure of the glass-silicon carbide bottom layer.

[0050] The third aspect of the present invention provides an FPC austenitic stainless steel reinforcement plate, the surface of which is coated with the composite coating according to the first aspect of the present invention.

[0051] Specifically, the FPC austenitic stainless steel reinforcement plate is used to reinforce the flexible circuit board, which can increase the strength of the flexible circuit board and extend its service life.

[0052] The basic principle of the present invention is described as follows:

[0053] The composite coating provided by the present invention contains a glass-silicon carbide bottom layer. The material composition of the raw glass powder is controlled. By adjusting the ratio of network outer oxides (Na2O, K2O and CaO), intermediate oxides (B2O3 and Al2O3), and network former oxide SiO2, a coating with a thermal expansion coefficient suitable for austenitic stainless steel is obtained, and the bonding strength of the coating to the steel substrate is improved by adding the bonding oxide CoO.

[0054] During high-temperature firing, the melting and spreading of the glass powder competes with the oxidation of the steel matrix. Once the glass powder melts and covers the steel surface, it will inhibit the oxidation of the steel. Once the steel is severely oxidized, a thicker oxidation product film will be generated, which will hinder the coverage of the glass at that location. By adjusting the thickness of the glass coating and the firing system, a coating with suitable size and uniform pore distribution can be obtained. By adding silicon carbide and controlling its size so that it is evenly dispersed in the glass matrix matrix, silicon carbide will oxidize during high-temperature firing and form a dense silicon oxide shell on its surface, inhibiting the continued oxidation of silicon carbide.

[0055] By rationally designing the glass composition and firing process, it is convenient to store the polytetrafluoroethylene lubricating phase and improve the mechanical bonding of the polytetrafluoroethylene layer. The silicon carbide particles in the coating act as a hard phase and have both self-lubricating and wear-resistant properties together with the polytetrafluoroethylene layer on the surface.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] 1) The composite coating provided by the present invention has a porous glass-silicon carbide bottom layer, which provides a basis for loading polytetrafluoroethylene to construct a surface lubricating film. The coating has excellent wear resistance, can withstand high loads within 20N, and maintain a long service life;

[0058] 2) The preparation method of the composite coating provided by the present invention has simple steps. By controlling the thickness of the glass-silicon carbide porous bottom layer and the sintering process, a porous structure with a suitable pore size and uniform distribution is prepared, and then the consolidation and penetration of polytetrafluoroethylene are achieved by the method of pulling, dipping and drying to ensure that it is not easy to fall off;

[0059] 3) The composite coating provided by the present invention is firmly bonded to the surface of the stainless steel substrate, has good self-lubricity and wear resistance, and can meet the performance requirements of the FPC reinforcement for the austenitic stainless steel reinforcement plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 is a three-dimensional morphology image of the coating in Examples 1-3;

[0061] Figure 2 is a two-dimensional topography image of the coating in Examples 1-3;

[0062] Figure 3 The SEM images of the glass coating in Example 1 at different magnifications;

[0063] Figure 4 The SEM images of the glass-silicon carbide coating in Example 2 at different magnifications;

[0064] Figure 5 The SEM images of the composite coating in Example 3 at different magnifications;

[0065] Figure 6 Statistical diagram of diameters of holes on the coating surface in Example 1 (a) and Example 2 (b);

[0066] Figure 7 Typical friction coefficient curves of the four coatings in Examples 1-4 under a load of 10N;

[0067] Figure 8 The comparison of average friction coefficient and wear rate of the four coatings in Examples 1-4 after friction with a load of 10N;

[0068] Fig. 9 The cross-sectional height information of the wear scars of the four coatings in Examples 1-4 after friction under a load of 10N;

[0069] Fig.10 The three-dimensional morphology of the wear tracks of the four coatings in Examples 1-4 after friction under a load of 10N;

[0070] Fig.11 The SEM images of the wear marks of the glass coating of Example 1 at different magnifications;

[0071] Fig.12 The SEM images of the wear scar of the glass-silicon carbide coating of Example 2 at different magnifications;

[0072] Fig.13 The SEM images of the wear scar of the glass-polytetrafluoroethylene coating of Example 4 at different magnifications;

[0073] Fig.14 The SEM images of the wear scar of the composite coating of Example 3 at different magnifications;

[0074] Fig.15 The typical friction coefficient curve of the composite coating under different loads of Example 3;

[0075] Fig.16 The average friction coefficient and wear rate of the composite coating under different loads of Example 3;

[0076] Fig.17 The three-dimensional morphology of the wear track of the composite coating under different loads of Example 3;

[0077] Fig.18 The typical friction coefficient curve of the composite coating of Example 3 under different friction times;

[0078] Fig.19 The average friction coefficient and wear rate of the composite coating of Example 3 at different friction times;

[0079] Fig. 20 The three-dimensional morphology of the wear track of the composite coating of Example 3 under different friction times;

[0080] Fig.21 This is a comparison chart of the friction coefficients of the composite coating of Example 3 of the present invention and common coatings in the prior art. DETAILED DESCRIPTION

[0081] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0082] 1. The composition of the glass powder used in the examples is shown in Table 1:

[0083] Table 1 Composition of glass powder in the embodiment

[0084] Components Content (wt%) <![CDATA[SiO2]]> 60.00 <![CDATA[B2O3]]> 10.86 <![CDATA[Al2O3]]> 5.25 <![CDATA[Na2O]]> 10.86 <![CDATA[K2O]]> 5.25 CaO 5.60 CoO 2.18

[0085] The preparation steps of glass powder are as follows: SiO2, B2O3, Al2O3, Na2O, K2O, CaO and CoO are weighed according to the proportion, ball-milled and mixed at a speed of 300 r / min for 30 minutes using a planetary ball mill, smelted at 1300°C for 3 hours, and water quenched to obtain a glass block; ball-milled the glass block at a speed of 400 r / min for 120 hours using a planetary ball mill, and passed through a 200-mesh sieve to obtain glass powder with a particle size of less than 74 μm.

[0086] 2. The diameter of the silicon carbide used in the example is 1 μm.

[0087] 3. The polytetrafluoroethylene emulsion used in the examples was purchased from Shanghai San Ai Fu, FR-302 polytetrafluoroethylene emulsion, the content of polytetrafluoroethylene in the emulsion was 60 wt %, and the particle size was 200 nm.

[0088] 4. The size of the stainless steel substrate used in the embodiment is 20×20×2.5 mm, and it is polished with 400-grit sandpaper before use.

[0089] Example 1

[0090] This embodiment provides a glass coating (GL), and the preparation steps are as follows:

[0091] S11, mixing glass powder and anhydrous ethanol at a solid-liquid ratio of 1g:10mL to obtain a slurry;

[0092] S21. Use an ultrasonic cleaner to ultrasonically treat the slurry to obtain a uniformly mixed suspension, and use a spray gun to spray it onto the surface of the stainless steel substrate. The spraying pressure is 0.3 MPa and the distance is 30 cm. After spraying, the substrate is placed in a drying furnace at 100°C for heat treatment to eliminate the solvent, and then placed in a muffle furnace at 800°C for 10 minutes. After air cooling, a glass coating (GL) attached to the surface of the stainless steel substrate is obtained.

[0093] Example 2

[0094] This embodiment provides a glass-silicon carbide coating (GLS), and the preparation steps are as follows:

[0095] S11, mixing glass powder and silicon carbide at a mass ratio of 20:1, and then mixing the powder raw material with anhydrous ethanol at a solid-liquid ratio of 1g:10mL to obtain a slurry;

[0096] S21. Use an ultrasonic cleaner to ultrasonically treat the slurry to obtain a uniformly mixed suspension, and use a spray gun to spray it onto the surface of the stainless steel substrate. The spraying pressure is 0.3 MPa and the distance is 30 cm. After spraying, the substrate is placed in a drying furnace at 100°C for heat treatment to eliminate the solvent, and then placed in a muffle furnace at 800°C for 10 minutes. After air cooling, a glass-silicon carbide coating (GLS) attached to the surface of the stainless steel substrate is obtained.

[0097] Example 3

[0098] This embodiment provides a composite coating (GLSP), the preparation steps are:

[0099] S11, mixing glass powder and silicon carbide at a mass ratio of 20:1, and then mixing the powder raw material with anhydrous ethanol at a solid-liquid ratio of 1g:10mL to obtain a slurry;

[0100] S21, using an ultrasonic cleaner to perform ultrasonic treatment on the slurry to obtain a uniformly mixed suspension, spraying it onto the surface of the stainless steel substrate using a spray gun, the spraying pressure is 0.3 MPa, the distance is 30 cm, and after spraying, the substrate is placed in a drying furnace at 100° C. for heat treatment to eliminate the solvent, and the substrate is placed in a muffle furnace at 800° C. for 10 minutes, and after air cooling, a glass-silicon carbide bottom layer attached to the surface of the stainless steel substrate is obtained;

[0101] S31. Immerse the stainless steel substrate with the glass-silicon carbide bottom layer in polytetrafluoroethylene emulsion, use a removal speed of 2 mm / min, an immersion duration of 1 min and a removal interval of 2 min, repeat 3 times, place the substrate in a tube furnace and sinter for 2 h at 380°C and 10 kPa vacuum conditions, and obtain a composite coating (GLSP) attached to the surface of the stainless steel substrate after cooling.

[0102] Example 4

[0103] This embodiment provides a glass-polytetrafluoroethylene coating (GLP), and the preparation steps are as follows:

[0104] S11, mixing glass powder and anhydrous ethanol at a solid-liquid ratio of 1g:10mL to obtain a slurry;

[0105] S21, using an ultrasonic cleaner to perform ultrasonic treatment on the slurry to obtain a uniformly mixed suspension, spraying it onto the surface of the stainless steel substrate using a spray gun, the spraying pressure is 0.3 MPa, the distance is 30 cm, and after spraying, the substrate is placed in a drying furnace at 100° C. for heat treatment to eliminate the solvent, and then placed in a muffle furnace at 800° C. for 10 minutes, and after air cooling, a glass coating attached to the surface of the stainless steel substrate is obtained;

[0106] S31. Immerse the stainless steel substrate with the glass coating in polytetrafluoroethylene emulsion, use a removal speed of 2 mm / min, an immersion duration of 1 min and a removal interval of 2 min, repeat 3 times, place the substrate in a tube furnace and sinter for 2 h at 380°C and 10 kPa vacuum conditions, and obtain a composite coating (GLP) attached to the surface of the stainless steel substrate after cooling.

[0107] Characterization and performance testing

[0108] 1. Observe the three-dimensional and two-dimensional morphologies of the coatings in Examples 1-3 using a laser confocal microscope:

[0109] Figure 1 is a three-dimensional morphology diagram of the coating in Examples 1-3, wherein: Figure 1 (a) is a three-dimensional morphology image of the glass coating (GL) of Example 1, Figure 1(b) is a three-dimensional morphology image of the glass-silicon carbide coating (GLS) of Example 2, Figure 1 (c) is a three-dimensional morphology image of the composite coating (GLSP) of Example 3. Figure 2 is a two-dimensional topography of the coating in Examples 1-3, wherein: Figure 2 (a) is a two-dimensional morphology image of the glass coating (GL) of Example 1, Figure 2 (b) is a two-dimensional morphology image of the glass-silicon carbide coating (GLS) of Example 2, Figure 2 (c) is a two-dimensional morphology image of the composite coating (GLSP) of Example 3. Figure 1 It can be seen that the coating surfaces prepared in Examples 1-3 all have a pore structure, and the pore structure on the glass-silicon carbide coating (GLS) is the most obvious; Figure 2 It can be seen that the pore depth of the glass coating (GL) in Example 1 is about 8.2 μm, the pore depth of the glass-silicon carbide coating (GLS) in Example 2 is about 8.4 μm, and the pore depth of the composite coating (GLSP) in Example 3 is about 6.1 μm. Compared with Example 2, the pore depth is reduced by about 2 μm, indicating that in the composite coating (GLSP) obtained by immersing the glass-silicon carbide coating (GLS) in a polytetrafluoroethylene emulsion, polytetrafluoroethylene is loaded in the pores and the filling depth is about 2 μm.

[0110] 2. Observe the microscopic morphology of the coating in Examples 1-3 using a field emission scanning electron microscope:

[0111] Figure 3 The SEM images of the glass coating in Example 1 at different magnifications are shown in FIG. Figure 3 (a) is a low-magnification SEM image. Figure 3 (b) is a high-magnification SEM image. Figure 3 It can be seen that in the glass coating (GL) prepared in Example 1, flaky Cr2O3 crystals are formed at the bottom of the holes. This is because the glass slurry is sprayed on the surface of the stainless steel substrate and cured at high temperature. The chromium (Cr) content in the stainless steel substrate is relatively high. Chromium is preferentially oxidized under high temperature conditions in the atmosphere, resulting in the formation of a Cr2O3 layer, which inhibits the rapid oxidation of iron. Cr2O3 will further oxidize and react with the sodium ions present in the glass matrix, so that dendritic NaCr3O4 crystals are precipitated from the glass matrix around these crystals. The reaction equation is 2Na2O+Cr2O3+1.5O2(g)=2Na2CrO4.

[0112] Figure 4 The SEM images of the glass-silicon carbide coating in Example 2 at different magnifications are shown in FIG. Figure 4 (a) is a low-magnification SEM image. Figure 4 (b) is a high-magnification SEM image. Figure 4It can be seen that compared with the pure glass coating in Example 1, the glass-silicon carbide coating prepared by adding silicon carbide in Example 2 has more holes; the dark particles on the surface of the coating are silicon carbide particles with a diameter of about 1 μm and sharp edges, and the particles of similar size but blurred edges that appear around the silicon carbide particles are believed to be silicon carbide particles oxidized during the high-temperature sintering process.

[0113] Figure 5 The SEM images of the composite coating in Example 3 at different magnifications are shown in FIG. Figure 5 (a) is a low-magnification SEM image. Figure 5 (b) is a high-magnification SEM image. Figure 5 It can be seen that the pores in the composite coating are filled with polytetrafluoroethylene. In the peripheral area of ​​the pores, the volume of the polytetrafluoroethylene layer shrinks due to drying and dehydration, resulting in microcracks. The nanoscale polytetrafluoroethylene particles melt at high temperature and connect with each other to form a porous network structure with a pore size less than 1μm.

[0114] Figure 6 The diameter statistics of the holes on the coating surface in Example 1 (a) and Example 2 (b) are shown in FIG. Figure 6 It can be seen that the average diameter of the holes on the glass coating (GL) in Example 1 is 89.9±32.6μm, and the holes account for 50.6% of the total coating area; the average diameter of the holes in the glass-silicon carbide coating in Example 2 reaches 120.45±42.6μm, and the holes account for 52.1% of the total coating area, and the number of small-diameter holes increases.

[0115] 3. Tribological tests were performed on the coatings in Examples 1-4:

[0116] The experimental method is as follows: at room temperature, a multifunctional tribometer (UMT TriboLab, Bruker) was used to evaluate the tribological properties of the sample coatings, using a ball-disk reciprocating friction test configuration with a 6mm diameter silicon nitride ball as the counterpart. The experimental parameters were set as follows: the reciprocating stroke was 5mm and the sliding speed was 10mm / s. A normal load of 10N was applied to the GL, GLS, GLP and GLSP coatings for 1800s. In addition, under the same test conditions, loads of 15N and 20N were applied to the GLSP coating for 3600s, 7200s, 14400s and 21600s, respectively, to evaluate its high load-bearing capacity and service life.

[0117] Figure 7 is the typical friction coefficient curve of the four coatings in Examples 1-4 under a load of 10N, Figure 7It can be seen that when the glass coating (GL) prepared in Example 1 and the glass-silicon carbide coating (GLS) prepared in Example 2 are subjected to friction with a load of 10N, the friction coefficient increases sharply immediately, indicating that the coating is damaged and the stainless steel substrate is rubbed; the friction coefficient of the glass-polytetrafluoroethylene coating (GLP) prepared in Example 4 increases slightly, but when the 10N load is continuously rubbed for 1800s, the friction coefficient also increases to close to 0.7, and the coating is also damaged; while the friction coefficient of the composite coating (GLSP) prepared in Example 3 remains basically unchanged during the entire friction process, indicating that the glass-silicon carbide-polytetrafluoroethylene composite coating provided by the present invention has excellent wear resistance and can keep the coating from being damaged for a long time.

[0118] Figure 8 The average friction coefficient and wear rate of the four coatings in Examples 1-4 after friction with a load of 10N are compared. Figure 8 It can be seen that, based on the glass coating (GL) prepared in Example 1, silicon carbide, silicon carbide and polytetrafluoroethylene, and polytetrafluoroethylene are added to the glass coating (GL) in Examples 2, 3, and 4, respectively. It can be seen that when only silicon carbide is added, the average friction coefficient of the glass-silicon carbide coating (GLS) in Example 2 is equivalent to that of the glass coating (GL) in Example 1, but the wear rate is significantly increased; when only polytetrafluoroethylene is added, the average friction coefficient and wear rate of the glass-polytetrafluoroethylene coating (GLP) in Example 4 are reduced, indicating that the wear resistance of the coating is improved to a certain extent; and the composite coating (GLSP) in Example 3 has a greatly reduced average friction coefficient and wear rate, indicating that adding silicon carbide and polytetrafluoroethylene to the glass coating can achieve a significant improvement in the wear resistance of the coating.

[0119] Fig. 9 is the cross-sectional height information of the wear scars of the four coatings in Examples 1-4 after friction under a load of 10N, Fig.10 The three-dimensional morphology of the wear tracks of the four coatings in Examples 1-4 after friction with a load of 10N, wherein: Fig.10 (a) is a three-dimensional topography of the wear track of the glass coating (GL) in Example 1, Fig.10 (b) is a three-dimensional topography of the wear track of the glass-silicon carbide coating (GLS) of Example 2, Fig.10 (c) is a three-dimensional topography of the wear track of the glass-polytetrafluoroethylene coating (GLP) of Example 4, Fig.10 (d) is a three-dimensional topography of the wear track of the composite coating (GLSP) of Example 3. Fig. 9 and Fig.10 It can be seen that compared with the glass coating (GL), glass-silicon carbide coating (GLS) and glass-polytetrafluoroethylene coating (GLP), the composite coating (GLSP) provided by the present invention has the shallowest wear pits and the smallest area, indicating that it has the best wear resistance.

[0120] Fig.11 The SEM images of the wear marks on the glass coating of Example 1 at different magnifications are shown, where: Fig.11 (a) is a low-magnification SEM image. Fig.11 (b) is a high-magnification SEM image. Fig.11 It can be seen that the glass coating has been damaged, showing adhesive-abrasive mixed wear, and has rubbed against the stainless steel substrate.

[0121] Fig.12 The SEM images of the wear marks of the glass-silicon carbide coating of Example 2 at different magnifications are shown in FIG. Fig.12 (a) is a low-magnification SEM image. Fig.12 (b) is a high-magnification SEM image. Fig.12 It can be seen that the glass-silicon carbide coating peeled off and micro cracks appeared on the surface.

[0122] Fig.13 The SEM images of the wear marks of the glass-polytetrafluoroethylene coating of Example 4 at different magnifications are shown, where: Fig.13 (a) is a low-magnification SEM image. Fig.13 (b) is a high-magnification SEM image. Fig.13 It can be seen that there is wear debris accumulation on both sides of the glass-PTFE coated friction track, and the debris is embedded in the holes of the loaded PTFE.

[0123] Fig.14 The SEM images of the wear marks of the composite coating of Example 3 at different magnifications are shown in FIG. Fig.14 (a) is a low-magnification SEM image. Fig.14 (b) is a high-magnification SEM image. Fig.14 It can be seen that the surface of the composite coating only shows shallow wear marks, and only plastic deformation of the surface polytetrafluoroethylene occurs.

[0124] Fig.15 is a typical friction coefficient curve of the composite coating under different loads in Example 3, Fig.15 It can be seen that the friction coefficient of the composite coating (GLSP) provided by the present invention is always very stable within the load range of 20N (1.1GPa).

[0125] Fig.16 are the average friction coefficient and wear rate of the composite coating under different loads in Example 3, Fig.16 It can be seen that the average wear rate and friction coefficient of the composite coating (GLSP) provided by the present invention under different loads are always at a low level, and the coating has excellent wear resistance.

[0126] Fig.17 The three-dimensional morphology of the wear track of the composite coating under different loads in Example 3 is shown in FIG. Fig.17It can be seen that the composite coating (GLSP) provided by the present invention can withstand a relatively large load in the range of 20N (1.1GPa).

[0127] Fig.18 is a typical friction coefficient curve of the composite coating of Example 3 under different friction times, Fig.18 It can be seen that the friction coefficient of the composite coating (GLSP) provided by the present invention is always very stable within 6 hours, indicating that the coating has a long service life.

[0128] Fig.19 are the average friction coefficient and wear rate of the composite coating of Example 3 at different friction times, Fig.19 It can be seen that the average friction coefficient and wear rate of the composite coating (GLSP) provided by the present invention at different friction times are always at a low level.

[0129] Fig. 20 The three-dimensional morphology of the wear track of the composite coating of Example 3 under different friction times is shown in FIG. Fig. 20 It can be seen that under different friction times, the three-dimensional morphology of the wear track of the composite coating (GLSP) provided by the present invention is basically consistent, indicating that the coating has a long service life.

[0130] Fig.21 This is a comparison chart of the friction coefficient of the composite coating of Example 3 of the present invention and the common coating of the prior art. Fig.21 It can be seen that the friction coefficient and the corresponding load of the composite coating (GLSP) provided by the present invention are in the red circle. Compared with the prior art, the composite coating (GLSP) can still maintain a very low friction coefficient under heavy load, indicating that it has excellent wear resistance.

[0131] The composite coating provided by the present invention has a simple preparation method, excellent friction resistance, and is firmly bonded to a stainless steel substrate, and can meet the application requirements of FPC to reinforce austenitic stainless steel, extend the service life of austenitic stainless steel, and improve the performance of flexible circuit boards.

Claims

1. A composite coating, characterized in that: The composite coating comprises a glass-silicon carbide bottom layer and a polytetrafluoroethylene surface layer; the glass-silicon carbide bottom layer has a pore structure; and polytetrafluoroethylene is loaded in the pores.

2. The composite coating according to claim 1, characterized in that: In the glass-silicon carbide bottom layer, the depth of the holes is 7-10 μm; and / or, the average diameter of the pores is 70-170 μm; And / or, the holes occupy 50-60% of the total area of ​​the glass-silicon carbide bottom layer.

3. The composite coating according to claim 1 or 2, characterized in that: The composite coating comprises the following preparation raw materials: glass powder, silicon carbide, polytetrafluoroethylene emulsion and dispersant.

4. The composite coating according to claim 3, characterized in that: The glass powder comprises the following raw materials in percentage by mass: 55-65% SiO2, 8-12% B2O3, 3-7% Al2O3, 8-12% Na2O, 3-7% K2O, 3-7% CaO, and 1-4% CoO.

5. The composite coating according to claim 3, characterized in that: The particle size of the glass powder is less than 75 μm; And / or, the diameter of the silicon carbide is 1-3 μm.

6. The composite coating according to claim 3, characterized in that: In the polytetrafluoroethylene emulsion, the content of the polytetrafluoroethylene is 50-70wt%; And / or, the particle size of the polytetrafluoroethylene is 180-200 nm.

7. The composite coating according to claim 3, characterized in that: The mass ratio of the glass powder to silicon carbide is (15-25):1; And / or, the ratio of the volume of the dispersant to the total mass of the glass powder and silicon carbide is (10-20) mL:1 g.

8. The method for preparing the composite coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing glass powder, silicon carbide and a dispersant to obtain a slurry; S2, spraying the slurry onto the surface of the stainless steel substrate and curing it to obtain a glass-silicon carbide bottom layer; S3, immersing the stainless steel substrate containing the glass-silicon carbide bottom layer in a polytetrafluoroethylene emulsion, and coating the substrate by pulling to obtain the composite coating.

9. The preparation method according to claim 8, characterized in that: In step S2, the curing temperature is 750-850°C and the curing time is 10-15 minutes; And / or, in the step S3, the immersion time is 1-2 min / time; the pulling coating speed is 2-4 mm / min, and the number of times is 2-4 times.

10. An FPC austenitic stainless steel reinforcement plate, characterized in that: The surface of the FPC austenitic stainless steel reinforcement plate is coated with the composite coating according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Temperature-resistant thermal-spray radar absorbing coating and preparation method of spraying powder thereof

    CN102758164A

  • Metal surfaces comprising a thin glass- or ceramic-type protective layer having high chemical resistance and improved non-stick properties

    CN102803560A

  • Composite coating on surface of 310S stainless steel and preparation method of composite coating

    CN117050560A

  • Improvements in the coating of articles with polytetrafluoroethylene

    GB1042012A

  • Method of making articles from porous ceramic and fibre materials based on quartz glass

    RU2514354C1